How the war in Ukraine affects food security - Walter Leal Filho and Mariia Fedoruk and João Henrique Paulino Pires Eustachio and Jelena Barbir and Tetiana Lisovska and Alexandros Lingos and Caterina Baars (Foods, 2023)
The war in Ukraine has caused severe disruption to national and worldwide food supplies. Ukraine is a major exporter of wheat, maize, and oilseeds, staples that are now suffering a war-triggered supply risk. This paper describes the background of the problem and illustrates current trends by outlining some of the measures that may be deployed to mitigate the conflict’s impacts on achieving SDG 2 (Zero hunger), especially focusing on ending hunger, achieving food security, improving nutrition, and promoting sustainable agriculture. In order to understand the main research strands in the literature that are related to food security in the context of wars, the authors adopted a bibliometric literature review based on the co-occurrence of terms technique, conducted with 631 peer-reviewed documents extracted from the Scopus database. To complement the bibliometric assessment, ten case studies were selected to narrow down the food insecurity aspects caused by the war in Ukraine. The co-occurrence analysis indicated four different thematic clusters. In the next stage, an assessment of the current situation on how war affects food security was carried out for each one of the clusters, and the reasons and possible solutions to food security were identified. Policy recommendations and theoretical implications for food security in the conflict context in Ukraine were also addressed.
Keywords: food security; Ukraine; war; agriculture; economics; public policies